2015
DOI: 10.1021/acs.iecr.5b02681
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Arrangement of Composite Drops in Two-Dimensional Microchannels Using Multiagent Simulations: A Design Perspective

Abstract: Drops can self-organize in two-dimensional (2D) microchannels to form ordered arrangements. Design of microchannels that result in a particular pattern of drops for a specific purpose is difficult and nonintuitive due to the inherent complexity of the drop dynamics. We address the problem of understanding the arrangement of composite drops inside a microchannel. A multiagent modeling strategy that was recently proposed by us is employed to understand this complex design problem. We consider the design of a dro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…The observed layering (a symmetry breaking instability) was caused by the infinitesimal local perturbations around the droplets entering the expansion channel. The results by Danny Raj et al 44 demonstrated even further the complexity of the formation of crystal-like structures in microfluidic device and called for further studies targeting a general framework to describe the observed structures.…”
Section: View Article Onlinementioning
confidence: 98%
See 1 more Smart Citation
“…The observed layering (a symmetry breaking instability) was caused by the infinitesimal local perturbations around the droplets entering the expansion channel. The results by Danny Raj et al 44 demonstrated even further the complexity of the formation of crystal-like structures in microfluidic device and called for further studies targeting a general framework to describe the observed structures.…”
Section: View Article Onlinementioning
confidence: 98%
“…In applications such as synthesis of anisotropic particles 41,42 or microfluidic crystals 43 formed by polymerised droplets having different properties, it is important to know how to inject the two droplets types in order to obtain the desired final structures. Numerical simulations carried out by Danny Raj et al 44 using the same geometry of Jose and Cubaud 24 studied the effect of the injection policy of two droplets types called 'A' and 'B', obtaining also some counterintuitive results. For instance, they demonstrated that an injection policy ABAB led to a microfluidic crystal where the succession of particles follow the order ABAB only when the crystal was 1D.…”
Section: View Article Onlinementioning
confidence: 99%